A Call for Arms! Supplying the Sultan's Army, 1916-1918. (2nd January 2021) - Bennett, Julian
Abstract : A common feature of Turkey's principal military-focused museums and of many local ones also, are displays of military equipment used in the First World War and in Turkey's War of Independence (1919–1923). In many cases these are rifles and bayonets supplied by Germany to the Ottoman Empire during two specific periods: from 1887 to 1903, when Germany supplied all the modern infantry weaponry used by the Ottoman army; and from 1916 to 1918, when Berlin answered the request from Constantinople for the latest models of their own small arms. This article looks into the circumstances behind that request and the German response, with a focus on the bayonets that were provided, as these are most often seen in places open to the public today. In addition, a brief account is provided on how these rifles and bayonets remained in service use, often in a modified form, until the 1950s.